Produtos de fermentação: Análise metabolômica na fermentação alcoólica do caldo de cana e acética de vinagres de banana, capacidade antioxidante de vinagres e o potencial fitotóxico da vinhaça da cana-de-açúcar - Luz, Dandara Alves (2022)
The fermentation is a biological process that includes a set of controlled reactions through which the simplest harmful substances complex, with the release of energy. Processes that involve fermentation are of great importance for the chemical, pharmaceutical and food industries, so the study of fermentation processes and products obtained from fermentation are of great interest. Alcoholic fermentation of sugarcane juice and acetic fermentation of Cavendish-type banana vinegar were investigated in different periods by mass spectrometry. A significant variation of compounds was identified throughout the fermentation process, such as the reduction of the signal corresponding to sucrose. In both fermentation processes there was an increase in the intensity of fatty acid signals, which is an indication that these substances are used as a lipid reserve, that is, a source of energy. Cavendish, Pome and Sucre subgroups banana vinegars were produced from natural fermentation. Organic acids, phenolic acids and sugars were the most abundant classes in the FTICR-MS, HS-CG-MS and SPME-CG-MS among the vinegars. The antioxidant capacity of the vinegars was 77.16%, 54, 26% and 73.02% for Cavendish, Pome and Sucre subgroups, respectively, these results showing a linear correlation with the total phenolic content of the samples. LC-ESI-MS analysis and LC-MS/MS multiple reaction monitoring (MRM) of the dichloromethane fraction of sugarcane vinasse (VDiCl) confirmed the proposed structures for the polyunsaturated acids 9,12,13 -trihydroxy10,15-octadecadienoyl and 9,12,13-trihydroxy-10-octadecenoyl/9,10,13-trihydroxy11-octadecenoyl (oxylipins). The phytotoxic evaluation of the purified fraction, rich in oxylipins, showed a reduction of 31.08%, at a concentration of 344 ppm, for the growth of roots of the high resistance weed, Ipomoea purpurea. This work demonstrates that the study of fermentation processes is of great value, since they can be a source of information for the improvement of biotechnological mechanisms and products obtained from this process, such as banana vinegar and vinasse, have high added value, as they are a source of bioactive compounds.